2023
DOI: 10.1103/physrevb.107.085417
|View full text |Cite
|
Sign up to set email alerts
|

Probing Majorana bound states through an inhomogeneous Andreev double dot interferometer

Abstract: In modern experiments with hybrid superconducting (SC)/semiconducting nanowires the presence of zero-energy Andreev bound states (ABSs), characterized by a partial overlap of the Majorana wave functions, is a common problem that significantly complicates the detection of a genuine Majorana bound state (MBS). In this article, taking into account spatial inhomogeneity of experimentally investigated nanowire samples, we study interference transport features of a curved heterostructure in which two normal wires (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…when superconducting bridge on Fig. 1 is connected only to the left wires [35,36]) demonstrated the persistance of the stability of the Fano peaks when transport symmetry changes (from symmetric to asymmetric). Using the spinless toy model it is shown that the fundamental π/2-phase shift for tunneling into the MMs of different type prevents the collapse of Fano resonances and BIC emergence.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…when superconducting bridge on Fig. 1 is connected only to the left wires [35,36]) demonstrated the persistance of the stability of the Fano peaks when transport symmetry changes (from symmetric to asymmetric). Using the spinless toy model it is shown that the fundamental π/2-phase shift for tunneling into the MMs of different type prevents the collapse of Fano resonances and BIC emergence.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, let us consider a limiting case of the above transport scheme by leaving only the left half of the system. In other words, in this section we turn to a Π-shaped device consisting of the LT and LB normal wires separated by the SW [35,36].…”
Section: Fano Resonances In Local Transport Schemementioning
confidence: 99%
“…Methods to probe MBS have been proposed by one of us [8] using Aharonov-Bohm interferometry that relies on the symmetry of the non-local conductance to Aharonov-Bohm flux. Further, interference of a different sort via Andreev double-dot interferometer [9] has also been used to detect MBS. Similarly, our original idea of detecting MBS by looking at the nonlocal Aharonov-Bohm conductance [8] has been extended to look at Coulomb blockade regime in [10] or the periodicity of the oscillations in [11,12], and to experiments in [13] to detect MBS.…”
mentioning
confidence: 99%